Snakebites in French Guiana: Conclusions of an international symposium. (May 2018) - Kallel, Hatem; Hommel, Didier; Mehdaoui, Hossein; Megarbane, Bruno; Resiere, Dabor
Abstract: A workshop on epidemiology and management of snakebites in French Guiana was performed at Cayenne, French Guiana from September 15 to September 16, 2017, under the auspices of the French Regional Health Agency (ARS) and the Pan American Health Organization (PAHO). The activity was attended by experts from France (Angers, Martinique, French Guiana, Guadeloupe, and Paris), Costa Rica, Brazil, Saint Lucia, and Surinam. The epidemiology, clinical manifestations, clinical grading and the management of snakebite in French Guiana were discussed. The conclusions of this symposium illustrated the urgent need to ensure accessibility of effective and safe polyvalent viperid antivenom in French Guiana. Finally, the results of this symposium have forged ties based on mutual goals and objectives. Highlights: Snake envenomation represents a major underestimated public health issue in Central and South America. In the Amazonian region, severe snakebites are caused by B. atrox, B. brasili, B. bilineatus, L. muta and Micrurus spp. Diagnosis of envenomation after snakebite is based on pain and edema at the anatomical site of the bite, and coagulopathy. Coagulopathy is very well established using the 20-min whole blood clotting test (WBCT20). The specific management of snakebite is the parenteral administration of antivenom.